More than Words: A global analysis of the socio-economic impact of Rich Interaction Applications (RIAs) - René Arnold; Christian Hildebrandt; Serpil Tas; Peter Kroon (International Telecommunications Society (ITS), 2017)
Applications such as iMessage, KakaoTalk, LINE, Signal, Skype, Snapchat, Threema, Viber, WhatsApp and WeChat have become an increasingly popular means of personal and business interaction. Surprisingly little academic effort has gone into understanding the nature and origin of these applications, yet. Policy makers and regulators on the other hand have developed pragmatic definitions of a group of applications that mimic functions of traditional Electronic Communications Services (ECS). Our paper explores whether this approach gives proper consideration to these applications' nature. Based on our indicative framework for delineating them from other OTT services, we use econometric modelling to approximate their global economic impact. We find that any static definition of these applications is bound to fall short of reality within a few months due their rapid innovation cycle. Nonetheless, we are able to identify functions that enable rich interactions among consumers and businesses as the common thread of 139 applications that we analysed. Thus, we sum them under the banner of Rich Interaction Applications (RIAs). Their constant innovation implies that they develop from baseline communications channels to applications that offer an increasingly large part of a `full internet experience'. With this in mind, our analysis places their economic impact between baseline telecommunications services' and the internet' impact. For a 10% increase in RIAs usage GDP for the 164 countries in our panel rises by 0.33% based on the years 2000 to 2015. In sum, policy makers and regulators ought to strive for framework conditions that enable or even better facilitate innovation as well as dynamic competition. Ultimately, these are the ingredients for realizing the largest benefits for consumers and the economy.
Keywords: L51; L86; O33; K23; 330; Competition; Regulation; Consumer Behavior; Telecommunications; Internet; ICT; OTT; Internet Services; Technological Change; Technology Adoption; Regulated Industries